PERILAKU PENCEGAHAN DAN PENGENDALIAN HIPERTENSI : STUDI PENGETAHUAN, SIKAP, PERILAKU (PSP) DAN KESEHATAN LINGKUNGAN PADA WANITA PASCA MENOPAUSE DI KOTA BOGOR - Woro Riyadina; Evi Martha; Athena Anwar (Puslitbang Upaya Kesehatan Masyarakat, 2018)
ABSTRACT Half of the women (48%) had hypertension at the age of menopause and the majority of hypertension was uncontrolled. For hipertensive patients, behavioral factors (knowledge, attitude and practice) and environment related to the prevention and control of blood pressure. This study explored further from the research data